2013
DOI: 10.1152/ajpregu.00246.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced in vivo hemoglobin polymerization in red blood cells of Gulf toadfish: a general role for hemoglobin aggregation in vertebrate hemoparasite defense?

Abstract: Two human hemoglobin (Hb) variants, Hb C and Hb S, are known to protect against Plasmodium falciparum malaria and have evolved repeatedly in malaria endemic areas. Both aggregate to insoluble crystals (Hb C) or polymers (Hb S) under certain physiological conditions, impair parasite growth, and may facilitate retention of infected red blood cells (RBCs) in the spleen. Given the profound effects of parasites on host evolution in general, and that RBC Hb concentration is often close to its solubility limit throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…This trend would be opposite if compensation were incomplete, as has been noted at high levels of CO 2 in certain species, where extracellular pH is partially compensated and intracellular pH is preferentially regulated (Brauner and Baker 2009). Overall, the plasma pH values were low compared to previous measurements from cannulated toadfish (Esbaugh et al 2012;Koldkjaer et al 2013), as would be expected for samples obtained by caudal puncture due to pCO 2 increases in anesthetized and air-exposed fish (Esbaugh et al 2015). It is also possible that samples from fish exposed to higher CO 2 levels, where blood pCO 2 was higher relative to ambient air, could have experienced greater CO 2 offgassing, raising pH.…”
Section: Discussionmentioning
confidence: 56%
“…This trend would be opposite if compensation were incomplete, as has been noted at high levels of CO 2 in certain species, where extracellular pH is partially compensated and intracellular pH is preferentially regulated (Brauner and Baker 2009). Overall, the plasma pH values were low compared to previous measurements from cannulated toadfish (Esbaugh et al 2012;Koldkjaer et al 2013), as would be expected for samples obtained by caudal puncture due to pCO 2 increases in anesthetized and air-exposed fish (Esbaugh et al 2015). It is also possible that samples from fish exposed to higher CO 2 levels, where blood pCO 2 was higher relative to ambient air, could have experienced greater CO 2 offgassing, raising pH.…”
Section: Discussionmentioning
confidence: 56%
“…While sickling in deer is particularly well-documented, the capacity for reversible haemoglobin polymerization has also been observed in a small coterie of other vertebrates10,50, including some species of fish50, mongoose51, and notably also goat and sheep ( Ovis aries )11,52. For most of these species, we have no information on sickling-associated genotypes and allelic diversity.…”
Section: Resultsmentioning
confidence: 99%
“…What are the ecological driving factors behind the maintenance of sickling (and non-sickling) alleles over evolutionary time? It has previously been suggested that haemoglobin polymerization might, by radically altering the intracellular environment of red blood cells, provide a generic defense mechanism against red blood cell parasites50. Deer certainly harbour a number of intra-erythrocytic parasites, including Babesia 57 and Plasmodium 58,59.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Hb inside RBCs is considered close to its solubility limit and chargechanging amino acid replacements on the surface of the Hb tetramer may affect the solubility of the protein, such as in the classic example of the human sickle Hb variant (HbS) that causes the aggregation of deoxygenated HbS and sickle cell disease (for review, see Bunn, 1997). Furthermore, the Hbs of several teleost fish species, including Atlantic cod, have been shown to be prone to in vivo polymerization (Hárosi et al, 1998;Koldkjaer and Berenbrink, 2007;Koldkjaer et al, 2013) and it is conceivable that the more negatively charged HbI-2 cold-water polymorph may permit higher RBC Hb concentrations than the warm-water HbI-1 polymorph and/or that the two different HbI polymorphs differentially affect the threshold or degree of Hb polymerization.…”
Section: Discussionmentioning
confidence: 99%